The Role of SIMAK-BMN Literacy on the Effect of Management Application of State, Human Resource Competence, and Organizational Commitment to the Quality of Financial Reports - Melia Dian Sukmawati; Suratno Suratno; Widarto Widarto (Syntax Corporation Indonesia, 2023)
The purpose of this study aims to determine what factors can affect the quality of financial reports at the Universitas Terbuka. A survey approach was carried out to obtain data from 17 Central Units and 39 Regional Units at the Universitas Terbuka. 102 data were obtained through purposive sampling. Methods of data analysis using simple linear regression and Moderated Regression Analysis (MRA). The results of the study partially prove that BMN needs planning, BMN administration, HR competency and organizational commitment have a positive effect on the quality of financial reports and SIMAK BMN literacy moderates the influence between BMN needs planning, BMN administration, HR competence and organizational commitment on the quality of financial reports.